PENGEMBANGAN ORGANISASI; IMPLEMENTASI DARI NILAI UNTUK KEBERLANJUTAN ORGANISASI - I Wayan Edi Arsawan; Ni Putu Santi Suryantini (Forum Manajemen STIMI Handayani Denpasar, 2016)
Organization development is a response to change, a complexeducational strategy intended to change the beliefs, attitudes, values, and structure of organizations so that they can better adapt to new technologies, markets, and challenges, and the dizzying rate of changeitself. Organizational development is the name that is being attached to total system, planned-change efforts for coping with the above-mentionedconditions.” (These conditions include four assertions about “today’schanging world,” five about “today’s business environment,” and six about “to day’s changing values”).This article discusses how the organization development become an importantelement of the way organizations deal with the dynamics of the competition. Becauseof the change (preparing the elements change) various obstacles and resistencesthat may occur. Noting the new culture that may arise from a shift in values that mayoccur, cultural resistences of the new policies that will arise and new planning thefuture.The purpose of this study is to provide an overview of how to prepare for changesin organizational management, preparing policies that supports the organization,reduce the risk of resistence and reduce the difference between the perception oforganizational elements and build a new culture that is in accordance with the visionand mission of the organization.Organizational development with regard to the value, new cultures, adopting newtechnologies, challenges and appropriate leadership style will create the conditionsand environment that is able to bring the organization to the objectives. It is indirectlydoing maintenance organizational elements that sustainability can be achieved.Sustainability means that the organization is not only an internal function but alsomaintain the market and customers.